IMPLEMENTASI TEORI BELAJAR GESTALT - Patriana (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2021)
This study describes the implementation of gestalt learning theory in the learning process in schools. The purpose of study was for implementating gestalt learning theory in the learning process in schools. This research uses qualitatiave research with the type of library research. Learning theory gestalt based on sightful learning process that promotes students understanding of the material taught by the teacher. The process of applying this theory is by discussing subject matter related to everyday life and having discussions with friends and teachers so that this approach can increase insight.